(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Several parasitic infections are associated with poor personal hygiene and environmental sanitation resulting in fruits containing eggs, cysts or larva of parasites. A survey of some fruits sold around Dutsin-ma metropolis in Katsina was carried out to identify the eggs, cyst and larva present on them. A total of 180 fruit pieces were examined using standard wet mount procedure and Kinyoun acid fast stain to detect presence of parasites. The percentage of fruits found with eggs, cysts or larvae of six parasites identified were eggs of hookworm (16.42%), Ascaris lumbricoides eggs (24.30%), Trichuris trichuira eggs (8.62%), Strongyloides stercoralis larvae (6.64%), immature cyst of Entamoeba histolytica (31.62%) and eggs of Taenia species (12.4%) respectively. Garden eggs had the highest percentage with parasites’ ova, cysts or larva (60.3%) followed by water melon (21.4%) and cucumber (12.12%), mangoes (10%), carrots (4.8%) and oranges (0%). The chi-square test showed significant (p<0.05) differences in number of fruits with parasitic infection. It is very important to encourage proper washing of fresh and raw fruits before they are sold or eaten which will thereby prevent transmission either at point of sell or consumption of fruits which infect via the oral route